Kappa Opioid Receptor Agonist Mesyl Sal B Attenuates Behavioral Sensitization to Cocaine with Fewer Aversive Side-Effects than Salvinorin A in Rodents - Bronwyn M. Kivell; Kelly F. Paton; Nitin Kumar; Aashish S. Morani; Aimee Culverhouse; Amy Shepherd; Susan A. Welsh; Andrew Biggerstaff; Rachel S. Crowley; Thomas E. Prisinzano (Molecules, 2018)
The acute activation of kappa opioid receptors (KOPr) produces antinociceptive and anti-cocaine effects, however, their side-effects have limited further clinical development. Mesyl Sal B is a potent and selective KOPr analogue of Salvinorin A (Sal A), a psychoactive natural product isolated from the plant Salvia divinorum. We assessed the antinociceptive, anti-cocaine, and side-effects of Mesyl Sal B. The anti-cocaine effects are evaluated in cocaine-induced hyperactivity and behavioral sensitization to cocaine in male Sprague Dawley rats. Mesyl Sal B was assessed for anhedonia (conditioned taste aversion), aversion (conditioned place aversion), pro-depressive effects (forced swim test), anxiety (elevated plus maze) and learning and memory deficits (novel object recognition). In male B6.SJL mice, the antinociceptive effects were evaluated in warm-water (50 °C) tail withdrawal and intraplantar formaldehyde (2%) assays and the sedative effects measured with the rotarod performance task. Mesyl Sal B (0.3 mg/kg) attenuated cocaine-induced hyperactivity and behavioral sensitization to cocaine without modulating sucrose self-administration and without producing aversion, sedation, anxiety, or learning and memory impairment in rats. However, increased immobility was observed in the forced swim test indicating pro-depressive effects. Mesyl Sal B was not as potent as Sal A at reducing pain in the antinociceptive assays. In conclusion, Mesyl Sal B possesses anti-cocaine effects, is longer acting in vivo and has fewer side-effects when compared to Sal A, however, the antinociceptive effects are limited.